Navigating Social Piety and State Stability in Indonesia’s Response to the Rohingya Refugee Crisis - Ali, Zezen Zainul; Muhajir , Muhammad; Mahmud, Zaeni; Mulyani, Maulidi (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
This study investigates Indonesia’s response to the Rohingya refugee crisis, focusing on the tension between humanitarian commitments and national stability. It explores how a predominantly Muslim country situated in the Global South and not party to the 1951 Refugee Convention manages the arrival of refugees amidst growing regional insecurity and limited institutional capacity. The study aims to critically examine how Indonesia’s reception of Rohingya refugees reflects both Islamic values of solidarity and the political, legal, and economic dilemmas that follow. Employing an interdisciplinary literature-based approach, the research synthesis legal, sociopolitical, and religious perspectives to understand state responses to refugee movements. Findings reveal two key dynamics. First, the Rohingya have faced systemic persecution in Myanmar, particularly through Burmanization policies that led to ethnic cleansing and genocide, constituting gross human rights violations. Second, Indonesia’s moral support for Rohingya Muslims highlights its humanitarian orientation, yet this position generates challenges across various sectors, including religion, law, security, and the economy. The arrival of refugees has sparked domestic debates around state sovereignty, social cohesion, and resource allocation. This study contributes to the literature on human rights and refugee protection in the Global South by offering insights into how non-signatory states balance humanitarian values with national interests. It underscores the need for more adaptive, context-sensitive policy frameworks that protect vulnerable populations while ensuring domestic stability. The study encourages a deeper understanding of refugee governance in transitional democracies, where ethical responsibility and political pragmatism often collide.